Comparison of landing biomechanics between male and female professional dancers - Orishimo, K.; Kremenic, I.; Liederbach, M.; Pappas, E.; Hagins, M. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
The gender disparity in the incidence of noncontact anterior cruciate ligament (ACL) injuries among athletes has been well documented. (Ireland, 1999) Studies of landing activities have revealed gender differences in lower extremity biomechanics that may place female athletes at increased relative risk. (Hewett et al, 2005) By contrast, the gender disparity in the incidence of ACL injuries among elite ballet and modern dancers is much less apparent, even though the activity is laden with jumping and landing activities. (Liederbach, in press) The low incidence of ACL injuries in dancers of both sexes coupled with the fact that they receive intensive training in jumping and landing from a young age seems to suggest that technique and training may play a more prominent role in the commonly-reported disparity in ACL injuries than gender-specific anatomical or hormonal factors. There is little research comparing landing biomechanics of male and female dancers. The purpose of this study was to compare lower extremity kinematics and kinetics during single-leg drop-landings between male and female professional dancers. Our hypothesis was that no difference in lower extremity biomechanics would exist between men and women dancers.